2006
DOI: 10.1007/s11262-005-6917-x
|View full text |Cite
|
Sign up to set email alerts
|

P1 Protein of Cocksfoot Mottle Virus is Indispensable for the Systemic Spread of the Virus

Abstract: Cocksfoot mottle sobemovirus (CfMV) encodes a non-conserved protein P1 from the 5' ORF1 of genomic RNA. The functions of CfMV P1 are unknown. In the current study we show that P1-deficient CfMV can replicate both in oat leaves and barley suspension culture cells but can not infect oat plants systemically. However, the absence of P1 reduces the efficiency of virus accumulation considerably. The infectivity of the mutant virus restores as a result of the spontaneous transversion. CfMV P1:EGFP shows a very limite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…3A), the CfMV icDNA (Meier et al, 2006) was linearized with Cfr42I, and the cohesive ends were filled by T4 DNA polymerase (Fermentas) treatment. RGMoV cDNA2 digested with Bsp68I and XmaJI was ligated into CfMV icDNA, cut by Cfr42I and XmaJI to create pT7CfMV:RGMoVrek2.…”
Section: Plasmidsmentioning
confidence: 99%
“…3A), the CfMV icDNA (Meier et al, 2006) was linearized with Cfr42I, and the cohesive ends were filled by T4 DNA polymerase (Fermentas) treatment. RGMoV cDNA2 digested with Bsp68I and XmaJI was ligated into CfMV icDNA, cut by Cfr42I and XmaJI to create pT7CfMV:RGMoVrek2.…”
Section: Plasmidsmentioning
confidence: 99%
“…The 5¢-ends of genomes start with an untranslated region, followed by short ORF1, that code for 109-186 residue-long sobemovirus proteins with low similarity to each other [4]. The ORF1 coded proteins have been suggested to have a role in systemic infection [5] and in suppression of posttranscriptional gene silencing [6]. The 3¢-proximally located sobemovirus ORFs code for coat proteins (CP) with a comparably low sequence identity (16-31%).…”
mentioning
confidence: 99%
“…It was previously reported that P1 of CfMV is indispensable for virus movement and accumulation in oats [19] and that it is a suppressor of RNA silencing [20]. However, it still remains unclear whether P1 facilitates virus spread as an RNA silencing suppressor or as a member of the movement RNP complex.…”
Section: Discussionmentioning
confidence: 99%